THE EFFECT OF FINANCIAL RATIOS ON FINANCIAL PROFITABILITY IN MANUFACTURING COMPANIES LISTED ON THE IDX IN 2022-2024 - Sahbany, Sri; Riscal, Detty Agustin; Irawansyah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of Current Ratio, Debt to Asset Ratio, Total Asset Turnover, Working Capital Turnover on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2022-2024. The population in this study consisted of 14 manufacturing companies listed on the Indonesia Stock Exchange during the 2022-2024 period. With purposive sampling, the analysis method used was multiple linear regression analysis assisted by the SPSS 25 application. Based on the results of data analysis, the variables used in this study were Current Ratio, Debt to Asset Ratio, Total Asset Turnover, Working Capital Turnover as independent variables and Return on Assets as the dependent variable. The results of this study indicate that Current Ratio has a positive but insignificant effect on profitability. Debt to Asset Ratio has a positive but insignificant effect on profitability. Total asset turnover has a negative but insignificant effect on profitability and working capital turnover has no effect on profitability of manufacturing companies listed on the Indonesia Stock Exchange.